(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Diabetes mellitus (DM) is a disease condition characterised by hyperglycemia; free radical and abnormal haematological indices. Vitamin C can reduce free radical generation and ameliorate adverse conditions of diabetes mellitus. The aim of the present study is to investigate the effect of vitamin C on platelet aggregation and electrolyte levels in Type 1 DM. Male Wistar rats were divided into four groups namely control, DM, DM +Vitamin C and Vitamin C groups. Rats were made diabetic with a single dose of streptozotocin (65 mg/kg) intraperitoneally. Vitamin C was administered orally to diabetic and normal rats at 200 mg/kg body weight for 28 days. Blood samples were analyzed for hematological parameters, platelet aggregation, and serum electrolyte levels. Blood glucose in DM+ Vitamin C group (9.9 ± 1.8 mmol/L) was significantly reduced (p<0.01) compared to DM group (32.2 ± 2.1 mmol/L) and significantly higher (p<0.05) than control (4.4 ± 0.8 mmol/L). Haemoglobin (Hb) concentration in DM group (12 ± 0.1 g/dL) was significantly reduced (p<0.01) when compared with control groups (14 ± 0.24 g/dL) and significantly increased (p<0.05) in the DM+vitamin C group (13.5 ± 0.5 g/dL) compared with the diabetic group. The mean corpuscular volume values in DM (68.66 ± 0.5 fL) and DM+vitamin C groups (68.11 ± 0.4 fL) were significantly higher (p<0.01) than the control (59.49 ± 0.5fL). Platelet count in DM group (523 ± 8.5 x109/L) was significantly raised (p<0.01) when compared to control (356 ± 6.2 x109/L) and significantly reduced (p<0.01) in DM+ vitamin C-treated group (385 ± 7.8 x109/L) compared with DM group. Platelet aggregation and serum sodium/potassium ratios was significantly reduced (p<0.01) in DM+vitamin C compared with DM group. These results suggest that oral vitamin C administration increases haemoglobin, reduced plasma glucose level, platelet count, serum sodium/potassium ion ratio and inhibits platelet aggregation in streptozotocin-induced DM in rats.